Perlindungan hukum terhadap anakSebagai konsumen video klip lagu di youtube - Azizah, Yulianti Noer, Dr. Kelik Wardiono, S.H., M.H, Darsono, S.H., M.H (2015)
Video clip is one of the media used to market products songs in order people can recognize. The continued development of technology easier for anyone , including children access video clips of songs through the site youtube, but actually the case is not all the substance video clips of song has fulfilled the provisions in Article 20 of the Indonesian Broadcasting Commission Regulation No. 02 / P / KPI / 03 / 2012 on the Program Standard Payload Sex in Song and Video Clips. The provision was intended to keep people, especially children from the influence of pornography contained in the title, lyrics and visualization video clips of the song. Based on the analysis that has been conducted on five of legislations, namely Act No. 8 of 1999 on Consumer Protection, Act No. 32 of 2002 on Broadcasting, Act No. 11 of 2008 on Information and Electronic Transaction, Act No. 44 of 2008 on Pornography and Act No. 23 of 2003 on Child Protection has yet to provide an optimal legal protection of children as consumers video clips of songs.